2018
DOI: 10.1016/j.jid.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ligase Trim21 Ubiquitylates and Stabilizes Keratin 17 to Induce STAT3 Activation in Psoriasis

Abstract: Keratin 17 (K17), a marker of keratinocyte hyperproliferation, is a type I intermediate filament that is overexpressed in psoriatic epidermis and plays a critical pathogenic role by stimulating T cells. However, the posttranslational modification of K17, which is reversible and targetable, has not been elucidated. Herein, we reported that K17 could be modified through ubiquitination that controlled its stability and led to the phosphorylation and nuclear translocation of its interactor signal transducers and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 45 publications
1
45
0
1
Order By: Relevance
“…TRIM21, which belongs to the TRIM family, is an E3 ubiquitin ligase with a RING domain. TRIM21 is widely involved in cell proliferation, differentiation, autophagy, innate immunity and migration [50][51][52][53]. Our previous mass spectrometry identified several E3 ligases include CHIP and TRIM21 as interacting proteins of PRMT5 in prostate cancer cells [11].…”
Section: Discussionmentioning
confidence: 94%
“…TRIM21, which belongs to the TRIM family, is an E3 ubiquitin ligase with a RING domain. TRIM21 is widely involved in cell proliferation, differentiation, autophagy, innate immunity and migration [50][51][52][53]. Our previous mass spectrometry identified several E3 ligases include CHIP and TRIM21 as interacting proteins of PRMT5 in prostate cancer cells [11].…”
Section: Discussionmentioning
confidence: 94%
“…Mass spectrometry identified E3‐ligase Trim21 in K17 ubiquitination, which promoted the stability of K17 in psoriatic keratinocytes via K63‐linked ubiquitination. The Trim21‐induced ubiquitination of K17 interacted with STAT3, promoting its activation and cell proliferation in psoriasis keratinocytes (Figure B) . This opens a new avenue for targeting ubiquitination in the potential treatment of psoriasis.…”
Section: Regulation Of K17mentioning
confidence: 87%
“…Keratin 17 (K17) is a marker of psoriasis that is undetectable in normal epidermis but markedly upregulated in psoriatic lesions ( 11 , 12 ). A recent study has suggested that IL-17 induces K17 in the epidermis by promoting the nuclear translocation of STAT3, which contributes to the pathogenesis of psoriasis ( 13 ).…”
Section: Introductionmentioning
confidence: 99%